PENGARUH LITERASI KEUANGAN, HERDING, PERSEPSI RISIKO, DAN ILLUSION OF CONTROL TERHADAP KEPUTUSAN INVESTASI EMAS LOGAM MULIA (Studi Kasus PT. Pegadaian Syari’ah Cabang Soebrantas Panam Pekanbaru) - Dwi Wahyuni; Roza Linda (Yayasan Azam Insan Cendikia, 2026)
This quantitative study was conducted with the main focus on examining the extent to which behavioral and cognitive variables—including Financial Literacy (X1), Herding (X2), Risk Perception (X3), and Illusion of Control (X4)—affect Investment Decisions (Y) of clients at PT Pegadaian Syariah Soebrantas Branch. The method used involved collecting primary data from 129 respondents. Sampling was carried out through purposive sampling, where respondents were selected based on criteria established by the researchers. The data collected using a Likert-scale questionnaire were then processed and analyzed using the Multiple Linear Regression method with the help of SPSS 21 statistical software. The variables of financial literacy, herding, risk perception, and illusion of control dominated the influence on investment decisions, contributing a total of 32%, while the remaining effect was influenced by other variables that were not tested. Keywords: Financial Literacy, Herding, Risk Perception, and Illusion of Control, Investment Decisions